Genistein from Vigna angularis Extends Lifespan in Caenorhabditis elegans - Lee, Eun Byeol (Biomol Ther (Seoul), 2015)
The seed of Vigna angularis has long been cultivated as a food or a folk medicine in East Asia. Genistein (4′,5,7-trihydroxyisoflavone), a dietary phytoestrogen present in this plant, has been known to possess various biological properties. In this study, we investigated the possible lifespan-extending effects of genistein using Caenorhabditis elegans model system. We found that the lifespan of nematode was significantly prolonged in the presence of genistein under normal culture condition. In addition, genistein elevated the survival rate of nematode against stressful environment including heat and oxidative conditions. Further studies demonstrated that genistein-mediated increased stress tolerance of nematode could be attributed to enhanced expressions of stress resistance proteins such as superoxide dismutase (SOD-3) and heat shock protein (HSP-16.2). Moreover, we failed to find genistein-induced significant change in aging-related factors including reproduction, food intake, and growth, indicating genistein exerts longevity activity independent of affecting these factors. Genistein treatment also led to an up-regulation of locomotory ability of aged nematode, suggesting genistein affects healthspan as well as lifespan of nematode. Our results represent that genistein has beneficial effects on the lifespan of C. elegans under both of normal and stress condition via elevating expressions of stress resistance proteins.